Sanitation and Personal Hygiene on Canteen Dharma Wanita Persatuan Airlangga University - Yuasadam, Noor Zain (JURNAL KESEHATAN LINGKUNGAN, 2018)
Airlangga University is one of the renowned universities in Indonesia which has a big share in the nation’s development. But it could run when supported with adequate facilities, among these facilities are one of the vital facilities where this facility is used as a dining area. Another term for this is the place to eat cafeteria where the canteen also has a stake in a healthy society also participated in it or make sick people in it, so that the cafeteria had to obtain special treatment in order to ensure the safety of food dijajakannya. But to refute it would require a special study where the cafeteria as its targets, especially female university canteen dharma airlangga who have close relations with the university management office airlangga. From the research that found that women getting the canteen dharma according 45.34 Permenkes No.1096/Menkes/Per/VI/2011 Concerning Sanitation Hygiene Jasaboga these results was considered inadequate and largely irrelevant to the prestigious universities in Indonesia.